The Impact of Mortality and Morbidity Meetings on Quality Improvement and Patient Safety - Kinzah Razzak Ghazi; Aiman Arif; Sharjeel Ahmad; Muhammad Osama Khan; Saqib Kamran Bakhshi (Journal of the Pakistan Medical Association, 2026)
Mortality and Morbidity meetings are vital forums for improving patient safety and fostering a culture of learning in healthcare. These meetings facilitate the identification of systemic vulnerabilities, root-cause analysis, and actionable quality improvement initiatives. They are especially crucial in resource-limited settings, where they address infrastructural and workforce constraints. However, barriers such as inconsistent attendance, lack of standardisation, underreporting, and limited follow-up hinder their effectiveness. To enhance their impact, standardised frameworks, multidisciplinary participation, and quality improvement tools, like the National Surgical Quality Improvement Programme, have been recommended. Expanding their reach through teleconferencing and publication of findings can further improve their utility. By addressing these challenges, these meetings can become transformative platforms for systemic change, professional development, and improved patient outcomes, particularly in resourceconstrained settings. The current narrative review was planned to examine Mortality and Morbidity meetings’ structure, impact, challenges and potential for optimisation. Keywords: Mortality, Morbidity conferences, Quality improvement, Patient safety, Medical errors, Clinical governance, Low- and middle-income countries, LMICs.